Effect of incorporating different polyaniline-surface modified nanosilica content into polyurethane-based quasi-solid-state electrolyte for dye-sensitized solar cells - Kai S. Liow; Coswald S. Sipaut; Mee, Ching Ung; Jedol Dayou (John Wiley & Sons Inc., 2020)
Polyaniline‐surface modified nanosilica (S‐PANi) was incorporated into polyurethane (PU) to form a polymer matrix able to entrap liquid electrolyte and to function as a quasi‐solid state electrolyte (QSE) in dye‐sensitized solar cells (DSSCs). Nanosilica was first synthesized via sol–gel technique and was post modified with aniline to form S‐PANi. The effects of introducing different S‐PANi content (5, 10, 15, and 20 wt%) on the nanoparticle distribution, surface morphology, surface porosity, thermal stability, and the structure of the PU matrix were analyzed using transmitted and reflected light microscopes, TGA and X‐ray powder diffraction. Additionally, polymer matrix absorptivity, conductivity, and ion diffusion of the formulated QSEs were investigated by using a digital analytical balance, the AC impedance method, and cyclic voltammetry. Lastly, all of the formulated quasi‐solid‐state electrolytes were applied for use in DSSCs wherein their charge recombination, photovoltaic performance, and lifespan were measured. The quasi‐solid‐state electrolyte based on 15 wt% S‐PANi (PU‐15%S‐PANi) exhibited the highest light‐to‐energy conversion efficiency, namely 3.17%, with an open circuit voltage of 708 mV, a short circuit current of 4.13 mA cm⁻², and a fill factor of 0.65.